2007
DOI: 10.1002/cncr.23049
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin and posttranslational glycan‐modified derivatives as serum biomarkers for the diagnosis of nonsmall cell lung cancer

Abstract: Ascending pathways to the telencephalon from the secondary gustatory nucleus (SGN), preglomerular tertiary gustatory nucleus (pTGN), and medial preglomerular nucleus (PGm) were examined by tract‐tracing experiments in goldfish Carassius auratus. Tracer injections to the SGN suggest the presence of direct ascending pathways to the supracommissural and the dorsal parts of the ventral telencephalic area, and the medial part of the dorsal telencephalic area (Dm), restricted to its ventral region. The SGN experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 82 publications
(125 reference statements)
2
56
1
1
Order By: Relevance
“…Patients with NSCLC exhibit higher plasma Hp protein levels than healthy donors and those levels correlate with aspects of disease progression, including clinical stage (19,20). Additionally, correlations between plasma Hp levels and patient prognosis have been reported in other types of cancer (32).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients with NSCLC exhibit higher plasma Hp protein levels than healthy donors and those levels correlate with aspects of disease progression, including clinical stage (19,20). Additionally, correlations between plasma Hp levels and patient prognosis have been reported in other types of cancer (32).…”
Section: Discussionmentioning
confidence: 97%
“…High levels of plasma Hp have been observed in a number of malignancies (13)(14)(15)(16)(17)(18). In patients with NSCLC, plasma Hp levels are higher than those of healthy donors and correlate with aspects of disease progression, including clinical stage (19,20). The presence of single nucleotide polymorphisms (SNPs) in the 5' flanking region of the Hp gene has been reported and some SNPs may affect plasma Hp levels (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…It is of interests that most of these identified proteins were lung cancer related. Of note is HP, which has been found in serum and used as biomarker for the diagnosis of NSCLC (2,36). The overexpression of this acute phase protein in human lung cancer tissues has been confirmed by immunohistochemistry and Western blot (37).…”
Section: Fig 5 Performance Of Biomarker Panelmentioning
confidence: 99%
“…According to the American Cancer Society, the major type of lung cancer is non-small-cell lung cancer (NSCLC) 1 , which comprises ϳ85% of lung cancers (1,2). Small cell lung cancer (SCLC) is another type of lung cancer, which represents about 15% of cases (3).…”
mentioning
confidence: 99%
“…Haptoglobin has been shown to be differentially glycosylated in prostate cancer patients compared with benign prostate hyperplasia patients or normal controls [27] and in non-small cell lung cancer [28]. Glycan analysis from Fujimura et al [27] has shown that haptoglobin has complex bi-antennary or tri-antennary N-linked glycan structures, most of which are heavily sialylated.…”
Section: Lectin Signatures For Putative Cancer Biomarkersmentioning
confidence: 99%